Surface treatment composition
By using a combination of surface treatment agents containing specific functional groups and electrolytes, the problem of high hydrophobicity in the prior art is solved, and efficient hydrophobicity and surface appearance protection under natural drying conditions is achieved.
Patent Information
- Application Number
- JP2023163036
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
AI Technical Summary
Existing surface treatment agents are difficult to maintain high hydrophobicity and do not damage the surface appearance on low surface free energy solid surfaces, especially under natural dry conditions.
A surface treatment agent combination is used which comprises a polymer with basic groups, ionic groups and hydrophobic groups, as well as a polymer with a relative charge of ionic polymer and hydrophobic groups, and an electrolyte. This combination enhances the adhesion of the polymer to the surface of low surface free energy solids by forming a polyelectric composite and hydrophobic interaction, and maintains high hydrophobicity under natural drying conditions.
The effect of maintaining high hydrophobicity without damaging the surface appearance of the surface is achieved on low surface free energy solid surfaces, especially under natural dry conditions.
Smart Images

Figure 2025053917000001 
Figure 2025053917000002 
Figure 2025053917000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a surface treatment composition and a surface treatment method. [Background technology]
[0002] Hydrophilization treatment of solid surfaces reduces the contact angle of the solid surface with water, making the solid surface more easily wetted by water, and is therefore expected to have effects such as anti-fogging and anti-static properties for glass, mirrors, etc., preventing frost formation on aluminum fins of heat exchangers, and imparting anti-fouling properties to the surfaces of bathtubs and toilets, etc., and therefore is used in various industrial fields, and studies on and methods for treating solid surfaces have been progressing.
[0003] For example, Patent Document 1 describes a hydrophilic treatment composition containing a hydrophilic treatment agent that exhibits excellent hydrophilicity for a long period of time, the hydrophilic treatment composition containing a copolymer containing a structural unit containing a betaine group and a structural unit having an aromatic group, an anionic surfactant, and water, and a hydrophilic treatment method in which the hydrophilic treatment composition is applied to a solid surface. Patent Document 2 describes a surface treatment composition for the purpose of providing a method for hydrophilizing a solid surface having a high hydrophilizing effect, which comprises a first polymer containing at least a constituent unit having a betaine group and a constituent unit having an ionic group, a second polymer containing at least a constituent unit having an ionic group having an opposite charge to the charge of the ionic group of the constituent unit having the ionic group, and an electrolyte, in which the equivalents of the betaine group of the constituent unit having a betaine group, the ionic group of the constituent unit having an ionic group of the first polymer, and the ionic group of the constituent unit having an ionic group of the second polymer satisfy specified conditions. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-94434 A [Patent Document 2] JP 2022-161634 A Summary of the Invention [Problem to be solved by the invention]
[0005] It has been found that when a surface treatment composition is applied to a solid surface having low surface free energy and the treated solid surface is dried from a wet state with water, a high hydrophilizing effect is obtained when rapid drying is performed, such as by spraying high-pressure nitrogen gas, but the hydrophilizing effect is reduced when drying is performed at a slow drying rate, such as natural drying. Therefore, there is a demand for further improvement in the hydrophilizing effect of surface treatment compositions and surface treatment methods. In addition, since conventional surface treatment compositions may impair the surface appearance of solids after treatment, there is also a demand for further improvement in the surface appearance of solids after treatment. An object of the present invention is to provide a surface treatment composition and a surface treatment method which, when applied to a solid surface having low surface free energy, have a high hydrophilizing effect without impairing the surface appearance of the solid after treatment, even when the treated solid surface is dried under conditions with a slow drying rate, such as natural drying. [Means for solving the problem]
[0006] The present inventors have found that the above problems can be solved by using a polymer that includes at least a constituent unit having a betaine group, a constituent unit having an ionic group, and a constituent unit having a hydrophobic group, a polymer that includes at least a constituent unit having an ionic group having an opposite charge to the charge of the ionic group of the constituent unit having an ionic group, and a constituent unit having a hydrophobic group, and an electrolyte. That is, the present invention provides the following [1] and [2]. [1] The following components (A), (B), and (C): (A) A polymer containing at least a structural unit (a1) having a betaine group, a structural unit (a2) having an ionic group, and a structural unit (a3) having a hydrophobic group. (B) A polymer comprising at least a structural unit (b1) having an ionic group having an opposite charge to the charge of the ionic group of the structural unit (a2), and a structural unit (b2) having a hydrophobic group. (C) Electrolyte A surface treatment composition comprising: [2] A surface treatment method, comprising applying the surface treatment composition according to [1] above to a solid surface having a surface free energy of less than 45 dyn / cm. Effect of the Invention
[0007] According to the present invention, it is possible to provide a surface treatment composition and a surface treatment method which, when applied to a solid surface having low surface free energy, have a high hydrophilizing effect without impairing the surface appearance of the solid after treatment, even when the treated solid surface is dried under conditions with a slow drying rate, such as natural drying. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Surface treatment composition] The surface treatment composition of the present invention comprises the following components (A), (B), and (C): (A) A polymer containing at least a structural unit (a1) having a betaine group, a structural unit (a2) having an ionic group, and a structural unit (a3) having a hydrophobic group. (B) A polymer comprising at least a structural unit (b1) having an ionic group having an opposite charge to the charge of the ionic group of the structural unit (a2), and a structural unit (b2) having a hydrophobic group. (C) Electrolyte Contains:
[0009] According to the present invention, when applied to a solid surface having a low surface free energy, even if the treated solid surface is dried under conditions with a slow drying rate such as natural drying, a high hydrophilization effect can be achieved without impairing the surface appearance of the solid after treatment. The reason for this effect is unclear, but is thought to be as follows. Conventionally, immediately after applying a surface treatment composition to a solid surface with low surface free energy, if the treated solid surface is in a wet state with water, a polymer thin film having a hydrophilic betaine group can be uniformly adsorbed on the solid surface, and a high hydrophilization effect can be exhibited. However, during the drying process of the treated solid surface, the polymer thin film having a hydrophilic betaine group becomes droplets, so-called dewetting phenomenon occurs, and the hydrophilization effect due to the hydrophilic betaine group of the polymer cannot be fully exhibited. This phenomenon occurs regardless of the drying speed during the drying process such as blowing nitrogen gas or natural drying. Therefore, in the surface treatment composition of the present invention, by containing the structural unit (b2) having a hydrophobic group, the affinity for a solid surface with low surface free energy is increased, so that even if the treated solid surface becomes dry, the dewetting phenomenon is unlikely to occur, and it is believed that the polymer thin film of the component (B) can be kept uniformly adsorbed on the solid surface. And, by containing the structural unit (b1) having an ionic group with an opposite charge to the charge of the ionic group of the structural unit (a2) of the component (A) in the component (B), a polyion complex is formed by the electrostatic interaction between the ionic group of the structural unit (a2) and the ionic group of the structural unit (b1), and the polymer thin film of the component (A) is also uniformly adsorbed on the solid surface via the component (B), and the hydrophilic effect of the hydrophilic betaine group of the structural unit (a1) of the component (A) is effectively exerted, and it is believed that a high hydrophilic effect can be exerted even when applied to a solid surface with low surface free energy. However, although components (A) and (B) are mutually adsorbed by the formation of a polyion complex, it is considered that not all of the ionic groups of these components are in a complexed state. Therefore, the adsorption force between components (A) and (B) is not strong, and when drying slowly from a wet state such as natural drying, it is considered that component (A) dewets during the drying process, and the hydrophilization effect of the betaine group is not fully exerted. Therefore, in the present invention, by including a structural unit (a3) having a hydrophobic group in component (A), the hydrophobic group of the structural unit (a3) of component (A) and the hydrophobic group of the structural unit (b2) of component (B) interact hydrophobically, reinforcing the adsorption force between components (A) and (B) due to the formation of a polyion complex, and the polymer thin film of component (A) can be uniformly adsorbed on the solid surface regardless of the drying speed after treatment, and as a result, it is considered that a high hydrophilization effect is exerted. Furthermore, in the present invention, component (C) improves the solubility of component (A) in the surface treatment composition, contributes to improving the blend stability, and enables the solid surface to be treated uniformly. As a result, it is believed that the surface appearance of the solid after treatment is improved and the hydrophilization effect can be improved.
[0010] In the present invention, the term "solid surface" refers to the interface between a solid and the atmosphere. The solid is not particularly limited, and examples thereof include glass, pottery, porcelain, enamel, tiles, ceramics, wood, metals such as aluminum, stainless steel, brass, etc., synthetic resins such as polycarbonate, polyethylene, polypropylene, melamine resin, polyamide resin, ABS resin, FRP, etc., natural fibers such as cotton, silk, wool, etc., synthetic fibers such as polyester, nylon, rayon, etc., hair, skin, nails, teeth, etc. The shape of the solid surface is not particularly limited.
[0011] In the present invention, the surface free energy of the solid is expressed by the critical surface tension γ C It can be determined by measuring Critical surface tension γ C is the critical surface tension γ CA liquid that has a surface tension lower than the critical surface tension γ C Solids with large surface tensions are easily wetted by many liquids, and have a critical surface tension of γ C This means that a solid with a small surface tension is difficult to wet. C is the surface tension γ L The contact angle θ is measured using a liquid with a known surface tension γ L Plot the cosine of the contact angle θ (cosθ) and extrapolate the value to cosθ = 1 as the critical surface tension γ c It can be measured by the Zisman method. The surface treatment composition of the present invention is preferably used for treating a solid surface having a surface free energy of less than 45 dyn / cm. As described above, the surface treatment composition of the present invention has high affinity for a solid surface having a low surface free energy because the component (B) contains the structural unit (b2) having a hydrophobic group, and furthermore, the hydrophobic group of the structural unit (a3) of the component (A) and the hydrophobic group of the structural unit (b2) of the component (B) interact hydrophobically with each other, reinforcing the adsorption force between the components (A) and (B) due to the formation of a polyion complex, and the polymer thin film of the component (A) can be uniformly adsorbed onto the solid surface regardless of the drying speed after treatment, so that a high hydrophilization effect can be achieved. From this viewpoint, the surface treatment composition of the present invention is preferably used as a hydrophilization treatment composition. In addition, from the above viewpoints, the surface free energy of the solid to which the surface treatment composition of the present invention is applied is more preferably less than 40 dyn / cm, even more preferably less than 35 dyn / cm, even more preferably less than 32 dyn / cm, even more preferably less than 30 dyn / cm, and is preferably 5 dyn / cm or more, more preferably 10 dyn / cm or more, even more preferably 20 dyn / cm or more. In the following description, in the case of application to a solid surface with low surface free energy, the hydrophilization effect when the treated solid surface is dried under conditions with a slow drying rate, such as natural drying, is simply referred to as the "hydrophilization effect."
[0012] <Component (A)> From the viewpoint of enhancing the hydrophilic effect, component (A) is a polymer that contains at least a structural unit (a1) having a betaine group (hereinafter also referred to as "structural unit (a1)"), a structural unit (a2) having an ionic group (hereinafter also referred to as "structural unit (a2)"), and a structural unit (a3) having a hydrophobic group (hereinafter also referred to as "structural unit (a3)"). Preferably, component (A) is a polymer that contains at least a structural unit (a1) having a betaine group, and a structural unit (a2-I) having a cationic group as the structural unit (a2) having an ionic group (hereinafter also referred to as "structural unit (a2-I)"). or an anionic betaine polymer AII (hereinafter also referred to as "anionic betaine polymer AII") that includes at least a structural unit (a1) having a betaine group, a structural unit (a2-II) having an anionic group as a structural unit (a2) having an ionic group (hereinafter also referred to as "structural unit (a2-II)"), and a structural unit (a3) having a hydrophobic group. Component (A) may be any of a block copolymer, a random copolymer, and an alternating copolymer.
[0013] In the present invention, the term "cationic group" refers to a cationic group or a group that can be ionized to become a cationic group. Examples of cationic groups include primary amino groups, secondary amino groups, tertiary amino groups, and quaternary ammonium groups. Among these, the cationic site of the betaine group is preferably a quaternary ammonium group from the viewpoint of enhancing the hydrophilic effect. In the present invention, the term "anionic group" refers to an anionic group or a group that can be ionized to become an anionic group. Examples of the anionic group include a carboxy group (-COOM 1 ), sulfonic acid group (-SO3M 1 ), phosphate group (-OPO3M 1 2) and the like. In the above chemical formula, M 1 represents a hydrogen atom, an alkali metal, ammonium or an organic ammonium. In the present invention, the "anionic polymer" is a polymer which has an anionic group and exhibits anionic properties as a whole. In the present invention, the "cationic polymer" is a polymer which has a cationic group and exhibits cationicity as a whole.
[0014] [Structural unit (a1)] From the standpoint of enhancing the hydrophilic effect, the component (A) contains a structural unit (a1) having a betaine group. In the present invention, the "betaine group" refers to a functional group having a cationic moiety and an anionic moiety, and the functional group as a whole does not have an electric charge. The cationic site of the betaine group is a positively charged atomic group, preferably a cationic group. The anionic portion of the betaine group is a negatively charged atomic group, preferably an anionic group.
[0015] From the viewpoint of enhancing the hydrophilic effect, the betaine group of the structural unit (a1) is preferably a sulfobetaine group, a phosphobetaine group, or a carbobetaine group, more preferably a sulfobetaine group or a phosphobetaine group, and even more preferably a sulfobetaine group, and the cationic site of these betaine groups is preferably a quaternary ammonium group. The betaine group may be of one type or of two or more types.
[0016] From the standpoint of enhancing the hydrophilic effect, the structural unit (a1) is preferably a structural unit having a betaine group represented by the following formula (1).
[0017] [ka] [In formula (1), R 1 ~R 3 are the same or different and each represents a hydrogen atom or an alkyl group having 1 or 2 carbon atoms, R 4is an alkylene group having 1 to 4 carbon atoms, or -Y 1 -OPO3 - -Y 2 - indicates Y 1 and Y 2 are the same or different and represent an alkylene group having 1 to 4 carbon atoms, R 5 and R 6 are the same or different and represent a hydrocarbon group having 1 to 4 carbon atoms, X 1 is an oxygen atom or NR 7 R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, X 2 is R 4 When is an alkylene group having 1 to 4 carbon atoms, R 17 SO3 - , or R 17 COO - R 17 represents an alkylene group having 1 to 4 carbon atoms which may have a hydroxyl group; X 2 is R 4 Ga-Y 1 -OPO3 - -Y 2 When - represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms.
[0018] The structural unit (a1) is preferably a structural unit having a sulfobetaine group, a phosphobetaine group, or a carbobetaine group. The structural unit (a1) may be one type, or may be two or more different types of structural units. The structural unit (a1) is, for example, a structural unit derived from a monomer (a1′) represented by the following formula (1′).
[0019] [ka] [In formula (1'), R 1 ~R 6 , X 1 , X 2 is the same as above.
[0020] In formulas (1) and (1′), R 1 ~R 6 , X 1 , X 2 Specific examples or preferred aspects of the above from the viewpoint of enhancing the hydrophilic effect are as follows. R 1 and R 2 is preferably a hydrogen atom. R 3 is preferably a hydrogen atom or a methyl group, and more preferably a methyl group. X 1 is preferably an oxygen atom. R 4 is preferably an alkylene group having 1 to 4 carbon atoms, more preferably an alkylene group having 2 or 3 carbon atoms, and even more preferably an alkylene group having 2 carbon atoms. R 5 and R 6 is preferably a methyl group or an ethyl group, and more preferably a methyl group. X 2 is R 4 When is an alkylene group having 1 to 4 carbon atoms, R 17 SO3 - , or R 17 COO - Preferably R 17 SO3 - R 17 represents an alkylene group having 1 to 4 carbon atoms which may have a hydroxyl group, is preferably an alkylene group having 1 to 3 carbon atoms or a hydroxyalkylene group having 2 to 4 carbon atoms, is more preferably an alkylene group having 1 to 3 carbon atoms, is even more preferably an alkylene group having 2 or 3 carbon atoms, and is still more preferably an alkylene group having 3 carbon atoms. X 2 is R 4 Ga-Y 1 -OPO3 - -Y 2 When - represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, preferably a hydrocarbon group having 1 to 4 carbon atoms, and more preferably a methyl group.
[0021] The structural unit (a1) is preferably a structural unit derived from at least one selected from the group consisting of monomers having a sulfobetaine group, such as N-(3-sulfopropyl)-N-(meth)acryloyloxyethyl-N,N-dimethylammonium betaine and N-(3-sulfopropyl)-N-(meth)acryloylamidopropyl-N,N-dimethylammonium betaine; monomers having a phosphobetaine group, such as 2-methacryloyloxyethyl phosphorylcholine; and monomers having a carbobetaine group, such as N-carboxymethyl-N-(meth)acryloyloxyethyl-N,N-dimethylammonium betaine and N-carboxymethyl-N-(meth)acryloylamidopropyl-N,N-dimethylammonium betaine. and more preferably a structural unit derived from at least one selected from the group consisting of a monomer having a sulfobetaine group and a monomer having a phosphobetaine group, even more preferably a structural unit derived from a monomer having a sulfobetaine group, still more preferably a structural unit derived from at least one selected from the group consisting of N-(3-sulfopropyl)-N-(meth)acryloyloxyethyl-N,N-dimethylammonium betaine and N-(3-sulfopropyl)-N-(meth)acryloylamidopropyl-N,N-dimethylammonium betaine, and still more preferably a structural unit derived from N-(3-sulfopropyl)-N-(meth)acryloyloxyethyl-N,N-dimethylammonium betaine. In this specification, "(meth)acryloyl" means "acryloyl" or "methacryloyl".
[0022] The content of the structural unit (a1) in all structural units of component (A) is, from the viewpoint of enhancing the hydrophilic effect, preferably at least 50 mol%, more preferably at least 60 mol%, even more preferably at least 70 mol%, still more preferably at least 75 mol%, still more preferably at least 80 mol%, still more preferably at least 85 mol%, and still more preferably at least 90 mol%, and from the same viewpoints as above, it is preferably at most 99.96 mol%, more preferably at most 99 mol%, even more preferably at most 97 mol%, and still more preferably at most 95 mol%. The content of each structural unit in all structural units of component (A) can be measured by analysis such as NMR, etc. It can also be calculated from the charge ratio of each monomer during the production of component (A).
[0023] [Structural unit (a2)] From the viewpoint of forming a polyion complex and enhancing the hydrophilic effect, the structural unit (a2) is preferably a structural unit (a2-I) having a cationic group or a structural unit (a2-II) having an anionic group. The cationic group and the anionic group are as described above.
[0024] (Structural unit (a2-I)) When component (A) is a cationic betaine polymer AI containing a structural unit (a2-I) having a cationic group, the structural unit (a2-I) is preferably a structural unit derived from a cationic group-containing polymerizable unsaturated monomer, and more preferably a structural unit having a cationic group represented by the following formula (2): The structural unit (a2-I) may be one type, or may be two or more different types of structural units. [ka] [In formula (2), R 8 ~R 10 are the same or different and each represents a hydrogen atom or an alkyl group having 1 or 2 carbon atoms, X 3 is an oxygen atom or NR 18 R18 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, R 11 represents an alkylene group having 1 to 4 carbon atoms, X 4 is N + R 12 R 13 R 14 X 5 or NR 15 R 16 R 12 ~R 16 are the same or different and each represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms; X 5 indicates an anion.
[0025] The structural unit (a2-I) is, for example, a structural unit derived from a monomer (a2-I') represented by the following formula (2').
[0026] [ka] [In formula (2'), R 8 ~R 11 , X 3 , X 4 is the same as above.
[0027] In formulas (2) and (2'), R 8 ~R 11 , X 3 , X 4 Specific examples or preferred aspects of the above from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilic effect are as follows. R 8 and R 9 is preferably a hydrogen atom. R 10 is preferably a hydrogen atom or a methyl group, and more preferably a methyl group. X 3 is preferably an oxygen atom. R 11 is preferably an alkylene group having 2 or 3 carbon atoms, and more preferably an alkylene group having 2 carbon atoms. X 4 is N + R 12 R 13 R 14 X 5 is preferred, R 12 , R 13 , R 14 From the same viewpoint as above, each of R is preferably a methyl group or an ethyl group, and more preferably R 12 , R 13 , and R 14 is an ethyl group. X 5 is preferably a halogen ion or C2H5SO4 - and more preferably C2H5SO4 - It is. X 4 NR 15 R 16 If R 15 and R 16 From the viewpoint of enhancing the hydrophilic effect and the ease of the quaternization reaction, is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0028] From the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilization effect, the structural unit (a2-I) is preferably a structural unit derived from an N,N-(dialkylamino)alkyl(meth)acrylic acid or a quaternary product thereof, more preferably a structural unit derived from a quaternary product of 2-(dialkylamino)alkyl (meth)acrylate, even more preferably a structural unit derived from at least one member selected from the group consisting of a quaternary product of 2-(dimethylamino)ethyl (meth)acrylate, a quaternary product of 2-(diethylamino)ethyl (meth)acrylate, and a quaternary product of 3-(dimethylamino)propyl (meth)acrylate, and still more preferably a structural unit derived from diethyl sulfate of 2-(dimethylamino)ethyl (meth)acrylate. In this specification, "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0029] (Structural unit (a2-II)) When component (A) is an anionic betaine polymer AII containing a structural unit (a2-II) having an anionic group, the structural unit (a2-II) is preferably a structural unit derived from an anionic group-containing polymerizable unsaturated monomer. Examples of the anionic group-containing polymerizable unsaturated monomer include a carboxyl group-containing polymerizable unsaturated monomer, a sulfonic acid group-containing polymerizable unsaturated monomer, and a phosphoric acid group-containing polymerizable unsaturated monomer. The structural unit (a2-II) may be one type, or may be two or more different types of structural units.
[0030] Examples of the carboxyl group-containing polymerizable unsaturated monomer include (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and 2-methacryloyloxymethylsuccinic acid. Examples of the sulfonic acid group-containing polymerizable unsaturated monomer include styrenesulfonic acid, 2-acrylamido-2-methylpropanesulfonic acid, and 3-sulfopropyl(meth)acrylate. Examples of the phosphoric acid group-containing polymerizable unsaturated monomer include vinyl phosphonic acid, vinyl phosphate, bis(methacryloyloxyethyl) phosphate, diphenyl-2-acryloyloxyethyl phosphate, and diphenyl-2-methacryloyloxyethyl phosphate. In this specification, "(meth)acrylate" means acrylate or methacrylate.
[0031] Among these, from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilization effect, the structural unit (a2-II) is preferably a structural unit derived from at least one selected from the group consisting of a carboxy group-containing polymerizable unsaturated monomer, a sulfonic acid group-containing polymerizable unsaturated monomer, and a phosphate group-containing polymerizable unsaturated monomer, more preferably a structural unit derived from at least one selected from the group consisting of a carboxy group-containing polymerizable unsaturated monomer and a sulfonic acid group-containing polymerizable unsaturated monomer, even more preferably a structural unit derived from a carboxy group-containing polymerizable unsaturated monomer, still more preferably a structural unit derived from at least one selected from the group consisting of (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and 2-methacryloyloxymethylsuccinic acid, and even more preferably a structural unit derived from (meth)acrylic acid.
[0032] The content of the structural unit (a2) in all structural units of component (A) is, from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilizing effect, preferably 0.02 mol% or more, more preferably 0.05 mol% or more, even more preferably 0.1 mol% or more, still more preferably 0.5 mol% or more, still more preferably 1 mol% or more, still more preferably 2 mol% or more, still more preferably 3 mol% or more, still more preferably 4 mol% or more, and still more preferably 5 mol% or more, and from the viewpoint of enhancing the hydrophilizing effect, preferably 30 mol% or less, more preferably 25 mol% or less, still more preferably 20 mol% or less, still more preferably 15 mol% or less, and still more preferably 10 mol% or less.
[0033] [Structural unit (a3)] Component (A) contains a structural unit (a3) having a hydrophobic group from the viewpoint of increasing the hydrophobic interaction with the hydrophobic group of component (B) and suppressing dewetting of component (A) on the solid surface, thereby enhancing the hydrophilization effect. The hydrophobic group of the structural unit (a3) is preferably a hydrocarbon group. Examples of the hydrocarbon group include saturated or unsaturated, straight-chain or branched-chain aliphatic hydrocarbon groups; alicyclic hydrocarbon groups such as a cyclohexyl group; and aromatic hydrocarbon groups such as a phenyl group. The hydrocarbon group may have a substituent as long as the effect of the present invention is not impaired. Examples of the substituent in the hydrocarbon group include halogen atoms; and oxyalkylene groups such as an oxyethylene group and an oxypropylene group. Furthermore, when the hydrocarbon group has 6 or more carbon atoms, the substituent on the hydrocarbon group may be a hydroxy group. In this case, the number of hydroxy groups is preferably 1 or 2.
[0034] The carbon number of the hydrocarbon group is 1 or more, from the viewpoint of enhancing hydrophobic interaction with the hydrophobic group of component (B) to suppress dewetting on the solid surface of component (A) and, as a result, enhancing the hydrophilization effect, and is preferably 30 or less, more preferably 22 or less, and even more preferably 18 or less. Specific examples of the hydrocarbon group include alkyl groups, aryl groups such as phenyl, orthotolyl, metatolyl, paratolyl, naphthyl, anthryl, phenanthryl, and biphenyl groups, aralkyl groups such as benzyl and phenethyl groups, alkenyl groups, and alkynyl groups. Among these, the hydrocarbon group is preferably at least one selected from the group consisting of linear or branched alkyl groups, phenyl, orthotolyl, metatolyl, paratolyl, biphenyl, and benzyl groups, more preferably at least one selected from the group consisting of linear or branched alkyl groups and benzyl groups, and even more preferably benzyl groups.
[0035] Among these, from the viewpoint of increasing the hydrophobic interaction with the hydrophobic group of the structural unit (b2) of component (B) and suppressing dewetting on the solid surface of component (A) and thereby enhancing the hydrophilization effect, the hydrophobic group of the structural unit (a3) is more preferably one that is present on a polymer side chain, and even more preferably at least one type of monovalent group selected from the group consisting of the following (i) and (ii): (i) A monovalent hydrocarbon group bonded to the polymer main chain via an ester bond (however, when the hydrocarbon group has 6 or more carbon atoms, the hydrocarbon group may have a hydroxy group as a substituent). (ii) A monovalent hydrocarbon group (excluding methyl groups) branched from the polymer main chain via a carbon-carbon bond.
[0036] The structural unit (a3) is preferably a structural unit derived from a hydrophobic-group-containing polymerizable unsaturated monomer, from the viewpoint of increasing the hydrophobic interaction with the hydrophobic group of component (B) to suppress dewetting of component (A) on the solid surface, thereby enhancing the hydrophilization effect. From the viewpoint of increasing the hydrophobic interaction with the hydrophobic group of component (B) to suppress dewetting on the solid surface and thereby enhancing the hydrophilization effect, it is preferable that the hydrophobic group-containing polymerizable unsaturated monomer is one capable of introducing the monovalent group (i) or the monovalent group (ii) as a hydrophobic group into the polymer skeleton. From the same viewpoint as above, the hydrophobic group-containing polymerizable unsaturated monomer is more preferably one or more selected from the group consisting of (meth)acrylic acid esters, styrene-based polymers, and olefins.
[0037] Examples of the (meth)acrylic acid ester include (meth)acrylic acid esters having a straight-chain or branched alkyl group such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (meth)acrylic acid esters having an alicyclic alkyl group such as cyclohexyl (meth)acrylate; and (meth)acrylic acid esters having a hydrocarbon group having 1 to 30 carbon atoms such as aromatic group-containing (meth)acrylic acid esters such as benzyl (meth)acrylate. esters; polyalkylene glycol (meth)acrylic acid esters such as polyethylene glycol (meth)acrylic acid ester (the average number of moles of alkylene oxide added is preferably 2 or more and 30 or less); alkoxy polyalkylene glycol (meth)acrylic acid esters such as methoxy polyethylene glycol (meth)acrylate, methoxy polypropylene glycol (meth)acrylate, octoxy (polyethylene glycol / polypropylene glycol copolymer) (meth)acrylate (the average number of moles of alkylene oxide added is preferably 2 or more and 30 or less); phenoxy polyalkylene glycol (meth)acrylic acid esters such as phenoxy ethylene glycol (meth)acrylate, phenoxy (polyethylene glycol / polypropylene glycol copolymer) (meth)acrylate (the average number of moles of alkylene oxide added is preferably 2 or more and 30 or less).
[0038] Examples of the styrene monomer include styrene, α-methylstyrene, and 2-methylstyrene. The number of carbon atoms in the olefin is preferably 4 or more and 10 or less, more preferably 4 or more and 8 or less. Examples of the olefin include 1-butene, isobutene, 1-pentene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-hexene, 1-octene, and diisobutylene (an isomer mixture of 2,4,4-trimethylpentene-1 and 2,4,4-trimethylpentene-2). The olefin is preferably one or more selected from the group consisting of 1-butene, isobutene, and diisobutylene. The hydrophobic-group-containing polymerizable unsaturated monomers may be used alone or in combination of two or more.
[0039] Among these, from the viewpoint of increasing the hydrophobic interaction with the hydrophobic group of component (B) to suppress dewetting on the solid surface of component (A) and thereby enhancing the hydrophilization effect, the hydrophobic-group-containing polymerizable unsaturated monomer is more preferably a (meth)acrylic acid ester having a hydrocarbon group having from 1 to 30 carbon atoms, even more preferably one or more selected from the group consisting of a (meth)acrylic acid ester having a linear or branched alkyl group, a (meth)acrylic acid ester having an alicyclic alkyl group, and an aromatic group-containing (meth)acrylic acid ester, and even more preferably methyl (meth)acrylate, ethyl (meth)acrylate, (meth)acrylic acid ester,
[0113] The acrylate or copolymer of the formula (I) and (II) is at least one selected from the group consisting of propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl (meth)acrylate, and even more preferably benzyl (meth)acrylate.
[0040] The content of the structural unit (a3) in all structural units of component (A) is, from the viewpoint of increasing the hydrophobic interaction with the hydrophobic groups of component (B) to suppress dewetting of component (A) on the solid surface, and as a result, to enhance the hydrophilization effect, preferably 0.02 mol% or more, more preferably 0.05 mol% or more, even more preferably 0.1 mol% or more, still more preferably 0.5 mol% or more, still more preferably 1 mol% or more, still more preferably 2 mol% or more, still more preferably 3 mol% or more, still more preferably 4 mol% or more, and still more preferably 5 mol% or more, and from the viewpoint of improving the solubility of component (A) to enhance the hydrophilization effect, preferably 30 mol% or less, more preferably 25 mol% or less, even more preferably 20 mol% or less, still more preferably 15 mol% or less, and still more preferably 10 mol% or less.
[0041] The molar ratio [((a2)+(a3)) / (a1)] of the combined content of structural units (a2) and structural units (a3) to the content of structural unit (a1) in all structural units of component (A) (hereinafter referred to as "molar ratio [((a2)+(a3)) / (a1)]") is, from the viewpoint of enhancing the hydrophilic effect, preferably 0.0004 or more, more preferably 0.01 or more, even more preferably 0.03 or more, still more preferably 0.05 or more, and still more preferably 0.08 or more, and from the same viewpoints as above, is preferably 0.5 or less, more preferably 0.45 or less, even more preferably 0.4 or less, still more preferably 0.35 or less, still more preferably 0.3 or less, still more preferably 0.2 or less, and still more preferably 0.12 or less. The molar ratio of the content of the structural unit (a3) to the content of the structural unit (a2) in all structural units of component (A) [(a3) / (a2)] is, from the viewpoint of enhancing the hydrophilic effect, preferably 0.1 or more, more preferably 0.3 or more, even more preferably 0.5 or more, and still more preferably 0.8 or more, and from the same viewpoints as above, is preferably 5 or less, more preferably 4 or less, even more preferably 3 or less, even more preferably 2 or less, even more preferably 1.5 or less, and still more preferably 1.2 or less. The molar ratio of the content of the structural unit (a3) to the content of the structural unit (a1) in all structural units of component (A) [(a3) / (a1)] is, from the viewpoint of enhancing the hydrophilic effect, preferably 0.01 or more, more preferably 0.03 or more, and even more preferably 0.05 or more, and from the same viewpoints as above, is preferably 0.7 or less, more preferably 0.5 or less, even more preferably 0.3 or less, still more preferably 0.2 or less, and even more preferably 0.1 or less.
[0042] When component (A) is a cationic betaine polymer AI, said component (A) may contain other structural units in addition to the structural units (a1), (a2-I), and (a3) within the scope of not impairing the effects of the present invention. Examples of other structural units include structural units derived from other monomers such as nonionic monomers such as alkyl(meth)acrylamides and vinylpyrrolidones; and anionic group-containing polymerizable unsaturated monomers. Examples of the alkyl(meth)acrylamide include N-alkyl(meth)acrylamide having an alkyl group having 1 to 22 carbon atoms, such as N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nt-butyl(meth)acrylamide, N,N-dimethylacrylamide, and N,N-diethyl(meth)acrylamide. As used herein, "(meth)acrylamide" means acrylamide or methacrylamide. Examples of the anionic group-containing polymerizable unsaturated monomer include the carboxyl group-containing polymerizable unsaturated monomers, sulfonic acid group-containing polymerizable unsaturated monomers, and phosphoric acid group-containing polymerizable unsaturated monomers exemplified for the structural unit (a2-II).
[0043] In addition, when component (A) is an anionic betaine polymer AII, said component (A) may contain other structural units than the structural unit (a1), the structural unit (a2-II), and the structural unit (a3) within a range that does not impair the effects of the present invention. Examples of other structural units include the above-mentioned nonionic monomers such as alkyl(meth)acrylamides and vinylpyrrolidones; and structural units derived from other monomers such as cationic group-containing polymerizable unsaturated monomers. Examples of the cationic group-containing polymerizable unsaturated monomer include the monomer represented by formula (2') exemplified above for the structural unit (a2-I).
[0044] The content of structural units other than the structural units (a1), (a2), and (a3) in all structural units of component (A) is preferably 30 mol% or less, more preferably 20 mol% or less, even more preferably 10 mol% or less, still more preferably 5 mol% or less, still more preferably 3 mol% or less, and even more preferably 1 mol% or less, and the content of other structural units may be 0 mol%.
[0045] From the viewpoint of hydrophilization effect, the total content of the structural units (a1), (a2), and (a3) in all structural units of component (A) is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, still more preferably 97 mol% or more, and still more preferably 99 mol% or more. The total content of the structural units (a1), (a2), and (a3) in all structural units of component (A) may be 100 mol%.
[0046] (Production of component (A)) The method for producing the component (A) is not particularly limited, and examples thereof include the following methods (x1) and (y1). (x1) A method for copolymerizing raw material monomers including the monomer (a1') represented by the formula (1'), the cationic group-containing polymerizable unsaturated monomer or the anionic group-containing polymerizable unsaturated monomer, and the hydrophobic group-containing polymerizable unsaturated monomer. (y1) A method of copolymerizing raw material monomers including a monomer represented by the following formula (1'-1), the cationic group-containing polymerizable unsaturated monomer or the anionic group-containing polymerizable unsaturated monomer, and the hydrophobic group-containing polymerizable unsaturated monomer to obtain a precursor of component (A), and then reacting the precursor with a betaining agent to betainize the precursor. Among these, the method (y1) is preferred from the viewpoints of availability of monomers and ease of production.
[0047] [ka] [In formula (1'-1), R 1 ~R 6 , X 1 is the same as formula (1), and the preferred embodiments are also the same as formula (1).
[0048] When using method (y1), for example, when the structural unit (a1) is a structural unit derived from a monomer having a sulfobetaine group, a precursor of component (A) can be obtained by copolymerizing raw material monomers including the monomer represented by formula (1'-1) above, and then reacting the precursor with a compound represented by formula (1'-2) or (1'-3) below as a betaine-forming agent to form a betaine. As the betaine-forming agent, the compound represented by formula (1'-2) below is preferred.
[0049] [ka] (In formula (1'-2), n is 1 or 2, preferably 1.)
[0050] ZR 17 -SO3M 2 (1'-3) [In formula (1'-3), Z represents Cl or Br, preferably Cl; R 17 represents an alkylene group having 2 to 4 carbon atoms which may have a hydroxyl group, and is preferably a 2-hydroxypropylene group; M 2 indicates Na or K.
[0051] The weight average molecular weight of component (A) is preferably 500 or more, more preferably 1,000 or more, even more preferably 5,000 or more, even more preferably 10,000 or more, even more preferably 30,000 or more, even more preferably 40,000 or more, from the viewpoint of enhancing the hydrophilic effect, and from the viewpoint of the blending stability of the surface treatment composition and the formation of a treated surface having a solid surface appearance after treatment, it is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, even more preferably 200,000 or less, even more preferably 100,000 or less, even more preferably 70,000 or less, even more preferably 50,000 or less. When component (A) is produced via the above-mentioned precursor, the weight average molecular weight of component (A) can be calculated from the weight average molecular weight of the precursor of component (A) measured by the method described in the Examples.
[0052] When the method (y1) is used as the method for producing component (A), the weight average molecular weight of the precursor of component (A) is preferably 500 or more, more preferably 1,000 or more, even more preferably 5,000 or more, even more preferably 10,000 or more, even more preferably 20,000 or more, even more preferably 30,000 or more from the viewpoint of enhancing the hydrophilic effect, and is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, even more preferably 200,000 or less, even more preferably 100,000 or less, even more preferably 70,000 or less, even more preferably 50,000 or less from the viewpoint of the blending stability of the surface treatment composition and the viewpoint of forming a treated surface having a solid surface appearance after treatment. The weight average molecular weight of the precursor of component (A) can be measured by the method described in the Examples.
[0053] <Ingredient (B)> Component (B) is a polymer that contains at least a structural unit (b1) having an ionic group having an opposite charge to the charge of the ionic group of structural unit (a2), and a structural unit (b2) having a hydrophobic group, from the viewpoint of suppressing dewetting on the solid surface and thereby enhancing the hydrophilization effect. Component (B) may be any one of a block copolymer, a random copolymer, and an alternating copolymer. Furthermore, each of the structural unit (b1) and the structural unit (b2) may be one type, or two or more different types of structural units.
[0054] The structural unit (b1) is preferably a structural unit (b1-I) having an anionic group or a structural unit (b1-II) having a cationic group. The anionic group and the cationic group are as described above.
[0055] The hydrophobic group of the structural unit (b2) is preferably a hydrocarbon group. Examples of the hydrocarbon group include saturated or unsaturated, straight-chain or branched-chain aliphatic hydrocarbon groups; alicyclic hydrocarbon groups such as a cyclohexyl group; and aromatic hydrocarbon groups such as a phenyl group. The hydrocarbon group may have a substituent as long as the effect of the present invention is not impaired. Examples of the substituent in the hydrocarbon group include halogen atoms; and oxyalkylene groups such as an oxyethylene group and an oxypropylene group. Furthermore, when the hydrocarbon group has 6 or more carbon atoms, the substituent on the hydrocarbon group may be a hydroxy group. In this case, the number of hydroxy groups is preferably 1 or 2.
[0056] The carbon number of the hydrocarbon group is 1 or more and preferably 30 or less, more preferably 22 or less, and further preferably 18 or less, from the viewpoint of suppressing dewetting on a solid surface and thereby enhancing the hydrophilic effect. Specific examples of the hydrocarbon group include alkyl groups, aryl groups such as phenyl, orthotolyl, metatolyl, paratolyl, naphthyl, anthryl, phenanthryl, and biphenyl groups, aralkyl groups such as benzyl and phenethyl groups, alkenyl groups, and alkynyl groups. Among these, the hydrocarbon group is preferably at least one selected from the group consisting of linear or branched alkyl groups, phenyl, orthotolyl, metatolyl, paratolyl, biphenyl, and benzyl groups, and more preferably at least one selected from the group consisting of linear or branched alkyl groups and benzyl groups.
[0057] Among these, from the viewpoint of suppressing dewetting on a solid surface and thereby enhancing the hydrophilizing effect, the hydrophobic group of the structural unit (b2) is more preferably one that is present on a polymer side chain, and even more preferably at least one type of monovalent group selected from the group consisting of (i) and (ii) below: (i) A monovalent hydrocarbon group bonded to the polymer main chain via an ester bond (however, when the hydrocarbon group has 6 or more carbon atoms, the hydrocarbon group may have a hydroxy group as a substituent). (ii) A monovalent hydrocarbon group (excluding methyl groups) branched from the polymer main chain via a carbon-carbon bond.
[0058] When component (B) has the monovalent group (i) or the monovalent group (ii) as the hydrophobic group, component (B) is preferably a vinyl polymer obtained by addition polymerization of a vinyl monomer such as a vinyl compound, a vinylidene compound, or a vinylene compound.
[0059] [Anionic polymer BI] When the ionic group of the structural unit (a2) is a cationic group, component (B) is an anionic polymer BI (hereinafter also referred to as "anionic polymer BI") that contains at least a structural unit (b1-I) having an anionic group as the structural unit (b1) and a structural unit (b2) having a hydrophobic group. From the viewpoint of enhancing the hydrophilic effect, the anionic polymer BI is preferably a vinyl polymer, and more preferably an anionic vinyl polymer containing at least a constituent unit derived from an anionic group-containing polymerizable unsaturated monomer as the constituent unit (b1-I) and a constituent unit derived from a hydrophobic group-containing polymerizable unsaturated monomer as the constituent unit (b2) (hereinafter, also referred to as "anionic vinyl polymer BI-1").
[0060] From the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilizing effect, the anionic group-containing polymerizable unsaturated monomer is preferably one or more selected from the group consisting of a carboxy group-containing polymerizable unsaturated monomer, a sulfonic acid group-containing polymerizable unsaturated monomer, and a phosphate group-containing polymerizable unsaturated monomer, more preferably a carboxy group-containing polymerizable unsaturated monomer, even more preferably one or more selected from the group consisting of (meth)acrylic acid, crotonic acid, itaconic acid, maleic acid, fumaric acid, citraconic acid, and 2-methacryloyloxymethylsuccinic acid, and even more preferably one or more selected from the group consisting of maleic acid and (meth)acrylic acid. The anionic group-containing polymerizable unsaturated monomers may be used alone or in combination of two or more.
[0061] From the viewpoint of suppressing dewetting on the solid surface and thus enhancing the hydrophilization effect, the hydrophobic group-containing polymerizable unsaturated monomer is preferably one capable of introducing the monovalent group (i) or the monovalent group (ii) as a hydrophobic group into the polymer skeleton. From the same viewpoint as above, the hydrophobic group-containing polymerizable unsaturated monomer is more preferably one or more selected from the group consisting of (meth)acrylic acid esters, styrene-based polymers, and olefins. Preferred examples of the (meth)acrylic acid ester and styrene-based monomer include the same as those exemplified for the component (A) described above. The number of carbon atoms in the olefin is preferably 4 or more and 10 or less, more preferably 4 or more and 8 or less. Examples of the olefin include 1-butene, isobutene, 1-pentene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-hexene, 1-octene, and diisobutylene (an isomer mixture of 2,4,4-trimethylpentene-1 and 2,4,4-trimethylpentene-2). The olefin is preferably one or more selected from the group consisting of 1-butene, isobutene, and diisobutylene. The hydrophobic-group-containing polymerizable unsaturated monomers may be used alone or in combination of two or more.
[0062] Among these, from the viewpoint of suppressing dewetting on a solid surface and thereby enhancing the hydrophilization effect, the hydrophobic group-containing polymerizable unsaturated monomer is more preferably at least one selected from the group consisting of (meth)acrylic acid esters and olefins having a hydrocarbon group having 1 to 30 carbon atoms, even more preferably at least one selected from the group consisting of (meth)acrylic acid esters having a linear or branched alkyl group, (meth)acrylic acid esters having an alicyclic alkyl group, aromatic group-containing (meth)acrylic acid esters, and olefins, and even more preferably methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-(meth)acrylic acid Preferably, the acrylate or acrylate is at least one selected from the group consisting of butyl, iso-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, and diisobutylene, and more preferably, the acrylate or acrylate is at least one selected from the group consisting of benzyl (meth)acrylate and diisobutylene.
[0063] When component (B) is an anionic polymer BI, component (B) may contain other structural units than the structural units (b1-I) and (b2) within the scope of the invention. Examples of other structural units include the above-mentioned nonionic monomers such as alkyl(meth)acrylamides and vinylpyrrolidones, and the above-mentioned structural units derived from other monomers such as cationic group-containing polymerizable unsaturated monomers.
[0064] When component (B) is an anionic polymer BI, from the viewpoint of enhancing the hydrophilizing effect, component (B) is preferably a vinyl polymer having a carboxy group, more preferably at least one selected from the group consisting of (meth)acrylic acid / (meth)acrylic acid ester copolymers, (meth)acrylic acid / styrene copolymers, maleic acid / diisobutylene copolymers, maleic acid / styrene copolymers, and salts thereof, and even more preferably at least one selected from the group consisting of (meth)acrylic acid / (meth)acrylic acid ester copolymers and maleic acid / diisobutylene copolymers.
[0065] [Cationic polymer BII] When the ionic group of the structural unit (a2) is an anionic group, component (B) is a cationic polymer BII (hereinafter also referred to as "cationic polymer BII") that contains at least a structural unit (b1-II) having a cationic group as the structural unit (b1) and a structural unit (b2) having a hydrophobic group.
[0066] From the viewpoint of enhancing the hydrophilic effect, the cationic polymer BII is preferably a vinyl polymer, and more preferably a cationic vinyl polymer containing at least a constituent unit derived from a cationic group-containing polymerizable unsaturated monomer as the constituent unit (b1-II) and a constituent unit derived from a hydrophobic group-containing polymerizable unsaturated monomer as the constituent unit (b2) (hereinafter also referred to as "cationic vinyl polymer BII-1"). The constituent unit derived from a cationic group-containing polymerizable unsaturated monomer is preferably a constituent unit having a cationic group represented by the following formula (2).
[0067] [ka] [In formula (2), R 8 ~R 11 , X 3 , X 4 is the same as above.
[0068] The structural unit (b1-II) is, for example, a structural unit derived from a monomer (b1-II') represented by the following formula (2').
[0069] [ka] [In formula (2'), R 8 ~R 11 , X 3 , X 4 is the same as above.
[0070] In formulas (2) and (2'), R 8 ~R 11 , X 3 , X 4 Specific examples or preferred aspects of the above from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilic effect are as follows. R 8 and R 9 is preferably a hydrogen atom. R 10 is preferably a hydrogen atom or a methyl group, and more preferably a methyl group. X 3 is preferably an oxygen atom. R 11 is preferably an alkylene group having 2 or 3 carbon atoms, and more preferably an alkylene group having 2 carbon atoms. X 4 N + R 12 R 13 R 14 X 5 If R 12 , R 13 , R 14From the same viewpoint as above, each of R is preferably a methyl group or an ethyl group, and more preferably R 12 , R 13 , and R 14 is an ethyl group. X 5 is preferably a halogen ion or C2H5SO4 - and more preferably C2H5SO4 - It is. X 4 NR 15 R 16 If R 15 and R 16 From the viewpoint of enhancing the hydrophilic effect and the ease of the quaternization reaction, is preferably a methyl group or an ethyl group, and more preferably a methyl group.
[0071] From the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilic effect, the constituent unit derived from a cationic group-containing polymerizable unsaturated monomer is preferably a constituent unit derived from an N,N-(dialkylamino)alkyl(meth)acrylic acid or a quaternary product thereof, more preferably a constituent unit derived from at least one selected from the group consisting of 2-(dimethylamino)ethyl (meth)acrylate, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, and quaternary products thereof, and even more preferably a constituent unit derived from 2-(dimethylamino)ethyl (meth)acrylate or a quaternary product thereof. The cationic group-containing polymerizable unsaturated monomers may be used alone or in combination of two or more.
[0072] From the viewpoint of suppressing dewetting on the solid surface and thereby enhancing the hydrophilization effect, the hydrophobic group-containing polymerizable monomer is preferably one capable of introducing the monovalent group (i) or the monovalent group (ii) as a hydrophobic group into the polymer skeleton. From the same viewpoint as above, the hydrophobic group-containing polymerizable unsaturated monomer is more preferably one or more selected from the group consisting of (meth)acrylic acid esters, styrene-based polymers, and olefins. Preferred examples of the (meth)acrylic acid ester and styrene-based monomer include the same as those exemplified above for component (A). Preferred examples of the olefin include the same olefins as those exemplified for the anionic polymer BI described above. The hydrophobic-group-containing polymerizable unsaturated monomers may be used alone or in combination of two or more.
[0073] Among these, from the viewpoint of suppressing dewetting on a solid surface and thereby enhancing the hydrophilization effect, the hydrophobic group-containing polymerizable unsaturated monomer is more preferably a (meth)acrylic acid ester having a hydrocarbon group having 1 to 30 carbon atoms, even more preferably one or more selected from the group consisting of a (meth)acrylic acid ester having a linear or branched alkyl group, a (meth)acrylic acid ester having an alicyclic alkyl group, and an aromatic group-containing (meth)acrylic acid ester, and even more preferably methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, (meth)acrylic acid The alkyl group is at least one selected from the group consisting of n-butyl, iso-butyl (meth)acrylate, sec-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-decyl (meth)acrylate, lauryl (meth)acrylate, myristyl (meth)acrylate, palmityl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, cyclohexyl (meth)acrylate, and benzyl (meth)acrylate, and is even more preferably benzyl (meth)acrylate.
[0074] When component (B) is a cationic polymer BII, said component (B) may contain other structural units than the structural units (b1-II) and (b2) within the range that does not impair the effects of the present invention. Examples of other structural units include the above-mentioned nonionic monomers such as alkyl(meth)acrylamides and vinylpyrrolidones; and structural units derived from other monomers such as the above-mentioned anionic group-containing polymerizable unsaturated monomers.
[0075] The content of the structural unit (b1) in all structural units of component (B) is, from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilic effect, preferably 30 mol% or more, more preferably 40 mol% or more, even more preferably 45 mol% or more, and even more preferably 50 mol% or more, and from the viewpoint of enhancing the hydrophilic effect, preferably 95 mol% or less, more preferably 80 mol% or less, even more preferably 70 mol% or less, even more preferably 65 mol% or less, even more preferably 60 mol% or less, and even more preferably 55 mol% or less. The content of the structural unit (b2) in all structural units of component (B) is, from the viewpoint of suppressing dewetting on the solid surface and, as a result, enhancing the hydrophilizing effect, preferably 0.02 mol% or more, more preferably 0.1 mol% or more, even more preferably 1 mol% or more, still more preferably 3 mol% or more, still more preferably 5 mol% or more, still more preferably 10 mol% or more, still more preferably 20 mol% or more, still more preferably 30 mol% or more, and still more preferably 40 mol% or more, and from the viewpoint of enhancing the hydrophilizing effect, preferably 70 mol% or less, more preferably 60 mol% or less, still more preferably 55 mol% or less, and still more preferably 50 mol% or less. From the viewpoint of hydrophilization effect, the total content of the structural units (b1) and the structural units (b2) in all the structural units of component (B) is preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more. The total content of the structural units (b1) and the structural units (b2) in all the structural units of component (B) may be 100 mol%. The content of each structural unit in all structural units of component (B) can be measured by analysis such as NMR, etc. It can also be calculated from the charge ratio of each monomer during the production of component (B).
[0076] When component (B) is an anionic polymer BI, the content of the structural unit (b1-I) in all structural units of the anionic polymer BI is, from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilizing effect, preferably 30 mol% or more, more preferably 40 mol% or more, even more preferably 45 mol% or more, and even more preferably 50 mol% or more, and from the viewpoint of enhancing the hydrophilizing effect, preferably 95 mol% or less, more preferably 80 mol% or less, even more preferably 70 mol% or less, even more preferably 65 mol% or less, even more preferably 60 mol% or less, and even more preferably 55 mol% or less. When component (B) is an anionic polymer BI, the content of the structural unit (b2) in all structural units of the anionic polymer BI is, from the viewpoint of suppressing dewetting on a solid surface and, as a result, enhancing the hydrophilizing effect, preferably 0.02 mol% or more, more preferably 0.1 mol% or more, even more preferably 1 mol% or more, still more preferably 3 mol% or more, still more preferably 5 mol% or more, still more preferably 10 mol% or more, still more preferably 20 mol% or more, still more preferably 30 mol% or more, and still more preferably 40 mol% or more, and from the viewpoint of enhancing the hydrophilizing effect, preferably 70 mol% or less, more preferably 60 mol% or less, still more preferably 55 mol% or less, and still more preferably 50 mol% or less. When component (B) is an anionic polymer BI, the total content of the structural unit (b1-I) and the structural unit (b2) in all structural units of the anionic polymer BI is, from the viewpoint of hydrophilization effect, preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, and still more preferably 95 mol% or more, and the total content of the structural unit (b1-I) and the structural unit (b2) in all structural units of component (B) may be 100 mol%. The content of each structural unit in the total structural units of the anionic polymer BI can be measured by analysis such as NMR, etc. Also, it can be calculated from the charge ratio of each monomer during the production of the anionic polymer BI.
[0077] When component (B) is a cationic polymer BII, the content of the structural unit (b1-II) in all structural units of the cationic polymer BII is, from the viewpoint of efficiently forming a polyion complex and enhancing the hydrophilic effect, preferably 30 mol% or more, more preferably 40 mol% or more, even more preferably 50 mol% or more, and even more preferably 60 mol% or more, and from the viewpoint of enhancing the hydrophilic effect, preferably 95 mol% or less, more preferably 90 mol% or less, even more preferably 85 mol% or less, even more preferably 80 mol% or less, even more preferably 75 mol% or less, and even more preferably 70 mol% or less. When component (B) is a cationic polymer BII, the content of the structural unit (b2) in all structural units of the cationic polymer BII is, from the viewpoint of suppressing dewetting on a solid surface and thereby enhancing the hydrophilic effect, preferably 0.02 mol% or more, more preferably 0.1 mol% or more, even more preferably 1 mol% or more, still more preferably 3 mol% or more, still more preferably 5 mol% or more, still more preferably 10 mol% or more, still more preferably 20 mol% or more, still more preferably 30 mol% or more, and from the viewpoint of enhancing the hydrophilic effect, preferably 70 mol% or less, more preferably 60 mol% or less, still more preferably 50 mol% or less, still more preferably 40 mol% or less. When component (B) is a cationic polymer BII, the total content of the structural unit (b1-II) and the structural unit (b2) in all structural units of the cationic polymer BII is, from the viewpoint of hydrophilization effect, preferably 70 mol% or more, more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, still more preferably 97 mol% or more, and still more preferably 99 mol% or more, and the total content of the structural unit (b1-II) and the structural unit (b2) in all structural units of component (B) may be 100 mol%. The content of each structural unit in the total structural units of the cationic polymer BII can be measured by analysis such as NMR, etc. Also, it can be calculated from the charge ratio of each monomer during the production of the cationic polymer BII.
[0078] The weight average molecular weight of component (B) is preferably 500 or more, more preferably 1,000 or more, even more preferably 5,000 or more, and even more preferably 10,000 or more from the viewpoint of enhancing the hydrophilic effect and the adsorption property of the surface treatment composition, and is preferably 10,000,000 or less, more preferably 1,000,000 or less, even more preferably 500,000 or less, even more preferably 200,000 or less, and even more preferably 100,000 or less from the viewpoint of the blending stability of the surface treatment composition and the viewpoint of improving the surface appearance of the solid after treatment. The weight average molecular weight of component (B) can be measured by the method described in the Examples.
[0079] <Ingredient (C)> The surface treatment composition of the present invention contains an electrolyte as component (C). In the present invention, component (C) is a component other than components (A) and (B). In the present invention, it is believed that component (C) improves the solubility of component (A) in the surface treatment composition, contributes to improving the blend stability, and enables the solid surface to be treated uniformly, thereby improving the surface appearance of the solid after treatment and improving the hydrophilization effect.
[0080] In the present invention, the term "electrolyte" refers to a compound that undergoes ion dissociation in water. Examples of component (C) include organic acids, inorganic acids, organic bases, inorganic bases, and salts thereof from the viewpoints of improving blend stability, improving the surface appearance of the solid after treatment, and enhancing the hydrophilizing effect. Examples of organic acids include monocarboxylic acids such as formic acid, acetic acid, propionic acid, and benzoic acid; dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, maleic acid, fumaric acid, and phthalic acid; polycarboxylic acids such as polyglutamic acid; hydroxycarboxylic acids such as glycolic acid, lactic acid, hydroxyacrylic acid, glyceric acid, malic acid, tartaric acid, and citric acid; acidic amino acids such as glutamic acid and aspartic acid; sulfonic acids such as methanesulfonic acid, N-methyltaurine, sulfamic acid, xylenesulfonic acid, p-toluenesulfonic acid, and benzenesulfonic acid; sulfate esters such as lauryl sulfate; and organic phosphate esters such as methyl phosphate and ethyl phosphate. Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, carbonic acid, thiocyanic acid, and phosphoric acid. The organic base includes alkanolamines such as monoethanolamine, diethanolamine, and triethanolamine. Examples of inorganic bases include hydroxides of alkali metals such as potassium, sodium, and lithium. Ammonia may also be used as the inorganic base. Examples of the salt include sodium chloride, potassium chloride, magnesium chloride, sodium citrate, potassium benzoate, ammonium chloride, sodium carbonate, dipotassium phosphate, and monoethanolamine sulfate. These may be used alone or in combination of two or more. When producing the surface treatment composition, component (C) may be prepared by mixing the above organic acid or inorganic acid with an organic base or inorganic base to form a salt in the surface treatment composition.
[0081] Among these, from the viewpoint of the compounding stability of the surface treatment composition, component (C) is preferably a low molecular weight electrolyte having a molecular weight of 200 or less, more preferably a salt, even more preferably a water-soluble inorganic salt, even more preferably one or more selected from the group consisting of alkali metal salts and metal salts of Group 2 elements, even more preferably one or more selected from the group consisting of sodium chloride, potassium chloride, and magnesium chloride, even more preferably one or more selected from the group consisting of sodium chloride and potassium chloride, and even more preferably sodium chloride. The solubility of the water-soluble inorganic salt in 100 g of water at 20° C. is preferably 10 g or more, more preferably 20 g or more, and even more preferably 30 g or more.
[0082] [Aqueous medium] The surface treatment composition of the present invention preferably contains an aqueous medium. Examples of the aqueous medium include water, lower alcohols such as ethanol and isopropyl alcohol, and low-molecular-weight diols and triols having 6 or less carbon atoms such as 1,3-butylene glycol, glycerin, ethylene glycol, and propylene glycol. Of these, the surface treatment composition preferably contains water.
[0083] [Other ingredients] The surface treatment composition of the present invention may contain other components in addition to the components (A), (B), and (C) to the extent that the effects of the present invention are not impaired. Examples of other components include amphoteric surfactants, antioxidants, silicones, aromatic alcohols, polymers other than the components (A) and (B), oils, vitamins, disinfectants, anti-inflammatory agents, antidandruff agents, preservatives, chelating agents, moisturizing agents, pearl agents, ceramides, fragrances, ultraviolet absorbing agents, etc.
[0084] The surface treatment composition of the present invention can be produced, for example, by blending components (A), (B), and (C) and, if necessary, other components, and mixing them using a known stirring device or the like.
[0085] The content or blending amount of component (A) in the surface treatment composition of the present invention is, from the viewpoints of enhancing the hydrophilizing effect, the blending stability of the surface treatment composition, and improving the surface appearance of the solid after treatment, preferably 0.01 mass% or more, more preferably 0.1 mass% or more, even more preferably 0.3 mass% or more, still more preferably 0.5 mass% or more, and still more preferably 0.8 mass% or more, and from the same viewpoints as above, preferably 15 mass% or less, more preferably 12 mass% or less, even more preferably 7 mass% or less, still more preferably 5 mass% or less, still more preferably 3 mass% or less, and still more preferably 2 mass% or less.
[0086] The content or blending amount of component (B) in the surface treatment composition of the present invention is, from the viewpoints of enhancing the hydrophilizing effect, the blending stability of the surface treatment composition, and improving the surface appearance of the solid after treatment, preferably 0.001 mass% or more, more preferably 0.01 mass% or more, and even more preferably 0.02 mass% or more, and from the same viewpoints as above, preferably 15 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, still more preferably 3 mass% or less, still more preferably 1 mass% or less, still more preferably 0.5 mass% or less, still more preferably 0.1 mass% or less, and still more preferably 0.05 mass% or less.
[0087] The mass ratio [(B) / (A)] of the content or amount of component (B) to the content or amount of component (A) in the surface treatment composition of the present invention (hereinafter referred to as "mass ratio [(B) / (A)]") is, from the viewpoint of enhancing the hydrophilizing effect, preferably 0.001 or more, more preferably 0.005 or more, even more preferably 0.01 or more, still more preferably 0.02 or more, and still more preferably 0.03 or more, and from the same viewpoints as above, is preferably 1 or less, more preferably 0.8 or less, even more preferably 0.5 or less, still more preferably 0.2 or less, still more preferably 0.1 or less, and still more preferably 0.05 or less.
[0088] The total content or total blending amount of component (A) and component (B) in the surface treatment composition of the present invention is, from the viewpoint of enhancing the hydrophilizing effect, preferably 0.01 mass% or more, more preferably 0.05 mass% or more, even more preferably 0.1 mass% or more, still more preferably 0.5 mass% or more, and still more preferably 1 mass% or more, and from the viewpoint of the blending stability and ease of handling of the surface treatment composition, as well as the cost, it is preferably 15 mass% or less, more preferably 12 mass% or less, even more preferably 10 mass% or less, still more preferably 7 mass% or less, still more preferably 5 mass% or less, still more preferably 3 mass% or less, and still more preferably 2 mass% or less.
[0089] The content or blending amount of component (C) in the surface treatment composition of the present invention is, from the viewpoints of blending stability of the surface treatment composition, improving the surface appearance of the solid after treatment, and enhancing the hydrophilizing effect, preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.5 mass% or more, still more preferably 0.8 mass% or more, and still more preferably 1 mass% or more, and from the viewpoints of blending ease and cost, preferably 15 mass% or less, more preferably 12 mass% or less, still more preferably 10 mass% or less, and still more preferably 5 mass% or less.
[0090] When water is used as the aqueous medium, the content or blending amount of the aqueous medium in the surface treatment composition of the present invention is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 70 mass% or more, still more preferably 80 mass% or more, even more preferably 85 mass% or more, and preferably 99 mass% or less.
[0091] [Surface treatment method] In the surface treatment method of the present invention, the surface treatment composition is preferably applied to a solid surface as a treatment target. That is, the surface treatment method of the present invention preferably includes a step of applying the surface treatment composition to a solid surface (hereinafter, also referred to as "step 1"). The solid to which the surface treatment composition is applied is as described above.
[0092] The method for applying the surface treatment composition to the solid surface in step 1 is not particularly limited, and examples thereof include the following methods (1-i) to (1-iii). (1-i) Method of immersing a solid in a surface treatment composition (1-ii) A method of spraying or applying a surface treatment composition to a solid surface (1-iii) A method of rinsing a solid surface with a surface treatment composition The ambient temperature when the surface treatment composition is applied to a solid surface is, from the viewpoint of enhancing the hydrophilizing effect and from the viewpoint of ease of work, preferably 5° C. or higher, more preferably 10° C. or higher, even more preferably 15° C. or higher, and is preferably 50° C. or lower, more preferably 40° C. or lower, even more preferably 30° C. or lower. The immersion time in the method (1-i) is, from the viewpoint of enhancing the hydrophilization effect and from the viewpoint of economy, preferably 0.1 minute or more, more preferably 0.3 minute or more, even more preferably 0.5 minute or more, still more preferably 1 minute or more, and is preferably 60 minutes or less, more preferably 50 minutes or less. The method of spraying or applying in the above method (1-ii) can be appropriately selected depending on the size (area) of the solid surface, etc. After spraying, the solution may be thinly spread using a sponge or the like. The amount of the surface treatment composition of the present invention applied to a solid surface is, for example, preferably 1 ml when the solid surface is made of polypropylene. 2 The maximum volume is 20 mL or more and 5,000 mL or less. The rinsing method in the method (1-iii) is preferably a method in which the solid surface is treated while flowing the surface treatment composition. When the solid surface to be treated is dirty, the solid surface may be cleaned while flowing the surface treatment composition.
[0093] From the viewpoint of enhancing the hydrophilization effect, step 1 is preferably step 1' in which the surface treatment composition is applied to the solid surface, and then an aqueous medium is brought into contact with the solid surface to which the surface treatment composition has been applied. By bringing the aqueous medium into contact in step 1', the concentration of component (C) contained in the surface treatment composition attached to the solid surface is reduced, and the formation of a polyion complex of components (A) and (B) is promoted, and the polymer thin film of component (A) is also uniformly adsorbed onto the solid surface via component (B), and the hydrophilic betaine group contained in component (A) can impart high hydrophilicity to the solid surface. The method of contacting the aqueous medium in step 1' is not particularly limited, and examples thereof include a method of immersing the solid surface to which the surface treatment composition has been applied in the aqueous medium, a method of spraying or applying the aqueous medium to the solid surface to which the surface treatment composition has been applied, and a method of rinsing the surface to which the surface treatment composition has been applied with the aqueous medium in a conventional manner. Among these, from the viewpoint of ease of operation, the method of rinsing the surface to which the surface treatment composition has been applied with the aqueous medium in a conventional manner is preferred. The aqueous medium used in step 1' is preferably, for example, water. The water used as the aqueous medium is not particularly limited, and tap water, distilled water, ion-exchanged water, hard water, soft water, etc. can be used. The amount of the aqueous medium used in step 1', for example, when the method of contacting with the aqueous medium is a method of rinsing with the aqueous medium, is preferably 500 parts by mass or more, more preferably 1000 parts by mass or more, even more preferably 1500 parts by mass or more, relative to 100 parts by mass of the surface treatment composition applied in step 1', and is preferably 5000 parts by mass or less, more preferably 4000 parts by mass or less, even more preferably 3000 parts by mass or less.
[0094] In the present invention, the solid surface to which the surface treatment composition is applied may be dried. Such a drying method is preferably natural drying or blow drying. Since the surface treatment composition of the present invention can exhibit a high hydrophilization effect even under conditions with a slow drying rate such as natural drying, natural drying may be used. The natural drying is preferably carried out in an environment having a temperature of 5° C. or higher and 50° C. or lower, and a humidity of 20% RH or higher and 90% RH or lower. EXAMPLES
[0095] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Various measurements were performed by the following methods.
[0096] (Weight average molecular weight of precursor of component (A)) The measurement was carried out using gel permeation chromatography under the following measurement conditions. [Measurement conditions] Column: Two "K-804L" (manufactured by Resonac Co., Ltd.) connected in series Column temperature: 40℃ Eluent: 1mmol / L dimethyllaurylamine, chloroform solution (Dimethyllaurylamine: Farmin DM2098: manufactured by Kao Corporation) Flow rate: 1.0mL / min Detector: Differential refractive index detector Sample size: 5mg / mL Standard material: polystyrene
[0097] (Weight average molecular weight of component (A')) The measurement was carried out using gel permeation chromatography under the following measurement conditions. [Measurement conditions] Column: Two "TSKgel α-M" columns (manufactured by Tosoh Corporation) connected in series Column temperature: 40℃ Eluent: 0.15mol / L Na2SO4, 1% by mass CH3COOH aqueous solution Flow rate: 1.0mL / min Detector: Differential refractive index detector Sample size: 5mg / mL Standard material: Pullulan
[0098] (Weight average molecular weight of component (B)) [Weight average molecular weight of anionic vinyl polymer BI-1] The measurement was carried out using gel permeation chromatography under the following measurement conditions. [Measurement conditions] Column: Two "TSKgel α-M" columns (manufactured by Tosoh Corporation) connected in series Column temperature: 40℃ Eluent: 60mmol / L H3PO4, 50mmol / L LiBr, DMF solution Flow rate: 1.0mL / min Detector: Differential refractive index detector Standard material: polystyrene
[0099] [Weight average molecular weight of cationic vinyl polymer BII-1] The measurement was carried out using gel permeation chromatography under the following measurement conditions. [Measurement conditions] Column: Two "K-804L" (manufactured by Resonac Co., Ltd.) connected in series Column temperature: 40℃ Eluent: 1mmol / L dimethyllaurylamine, chloroform solution (Dimethyllaurylamine: Farmin DM2098: manufactured by Kao Corporation) Flow rate: 1.0mL / min Detector: Differential refractive index detector Standard material: polystyrene
[0100] Production Example 1 (Production of Polymer A1) (Process A-1) In a separable flask with a capacity of 500 mL, 87.73 g of ethanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 34.28 g of 2-(dimethylamino)ethyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 3.99 g of a 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate, and 2.13 g of benzyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were placed, and degassed by nitrogen bubbling. Thereafter, the contents in the separable flask were heated to 65°C, and a solution obtained by mixing 0.61 g of V-65B (trade name, 2,2'-azobis(2,4-dimethylvaleronitrile), manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) (hereinafter referred to as "V-65B") and 5.00 g of ethanol was added thereto to initiate polymerization. Six hours after the start of polymerization, reprecipitation was carried out with hexane (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) The precipitated polymer was vacuum dried at 80° C. to obtain a polymer. The 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate was obtained by mixing 2-(dimethylamino)ethyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) and diethyl sulfate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) in a molar ratio of (1:1). (Process A-2) In a separable flask with a capacity of 200 mL, 10.00 g of the polymer obtained in step A-1 and 40.00 g of trifluoroethanol (manufactured by Tokyo Chemical Industry Co., Ltd.) were placed to dissolve the polymer. Thereafter, the contents in the separable flask were heated to 50°C, and 7.32 g of 1,3-propane sultone (manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise over 30 minutes to carry out a reaction. After the dropwise addition was completed, the mixture was aged at 50°C for 5 hours, and then re-precipitated with methanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.). The precipitated polymer was vacuum dried at 80°C to obtain polymer A1 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / methacrylic acid 2-(dimethylamino)ethyl diethyl sulfate / benzyl methacrylate copolymer). The content of the structural unit (a1), the content of the structural unit (a2), and the content of the structural unit (a3) of polymer A1 are shown in Table 1. The weight average molecular weight of the precursor of polymer A1 is shown in Table 1.
[0101] Production Example 2 (Production of Polymer A2) In Production Example 1, the amount of ethanol initially put into the separable flask in step A-1 was changed to 64.5 g, 2-(dimethylamino)ethyl methacrylate to 25.97 g, and the amount of 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate to 3.02 g, 2.13 g of benzyl methacrylate was changed to 1.31 g of butyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), V-65B was changed to 0.46 g, and the amount of 1,3-propane sultone used in step A-2 was changed to 7.39 g. In the same manner as in Production Example 1, except for this, polymer A2 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / 2-(dimethylamino)ethyl methacrylate diethyl sulfate / butyl methacrylate copolymer) was obtained. The content of the structural unit (a1), the content of the structural unit (a2), and the content of the structural unit (a3) of the polymer A2 are shown in Table 1. In addition, Table 1 shows the weight average molecular weight of the precursor of the polymer A2.
[0102] Production Example 3 (Production of Polymer A3) In Production Example 1, the amount of ethanol initially put into the separable flask in step A-1 was changed to 69.5 g, 21.06 g of 2-(dimethylamino)ethyl methacrylate, 2.65 g of a 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate, 6.29 g of benzyl methacrylate, and 0.44 g of V-65B, and the amount of 1,3-propane sultone used in step A-2 was changed to 7.19 g, and the same procedure was followed to obtain polymer A3 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / 2-(dimethylamino)ethyl diethyl methacrylate sulfate / benzyl methacrylate copolymer). The content of the structural unit (a1), the content of the structural unit (a2), and the content of the structural unit (a3) of polymer A3 are shown in Table 1. The weight average molecular weight of the precursor of polymer A3 is also shown in Table 1.
[0103] Production Example 4 (Production of Polymer A4) In Production Example 1, the amount of ethanol initially put into the separable flask in step A-1 was changed to 64.5 g, 2-(dimethylamino)ethyl methacrylate to 17.66 g, 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate to 9.51 g, benzyl methacrylate to 2.83 g, and V-65B to 0.39 g, and the amount of 1,3-propane sultone used in step A-2 was changed to 6.46 g, and the procedure was repeated to obtain polymer A4 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / 2-(dimethylamino)ethyl diethyl methacrylate sulfate / benzyl methacrylate copolymer). The content of the structural unit (a1), the content of the structural unit (a2), and the content of the structural unit (a3) of polymer A4 are shown in Table 1. The weight average molecular weight of the precursor of polymer A4 is also shown in Table 1.
[0104] Production Example 5 (Production of Polymer A5) In Production Example 1, the amount of ethanol and 2-(dimethylamino)ethyl methacrylate initially put into the separable flask in step A-1 were changed to 64.5 g and 27.46 g, respectively, and 3.99 g of a 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate was changed to 0.93 g of methacrylic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), benzyl methacrylate was changed to 1.71 g, V-65B was changed to 0.48 g, and 1,3-propane sultone used in step A-2 was changed to 7.52 g. Polymer A5 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / methacrylic acid / benzyl methacrylate copolymer) was obtained in the same manner as above, except that the content of the structural unit (a1), the content of the structural unit (a2), and the content of the structural unit (a3) of polymer A5 were changed to Table 1. The weight average molecular weight of the precursor of polymer A5 is shown in Table 1.
[0105] Production Example 6 (Production of Polymer A'1) In Production Example 1, the amount of ethanol initially put into the separable flask in step A-1 was changed to 87.73 g, the amount of 2-(dimethylamino)ethyl methacrylate was changed to 36.39 g, and the amount of 90% aqueous solution of 2-(dimethylamino)ethyl methacrylate diethyl sulfate was changed to 4.01 g, V-65B was changed to 0.61 g, benzyl methacrylate was not added, and the amount of 1,3-propane sultone used in step A-2 was changed to 7.78 g. In the same manner, polymer A'1 (N-(3-sulfopropyl)-N-methacryloyloxyethyl-N,N-dimethylammonium betaine / 2-(dimethylamino)ethyl methacrylate diethyl sulfate copolymer) was obtained. The content of the structural unit (a1), the content of the structural unit (a2), and the weight average molecular weight of polymer A'1 are shown in Table 1.
[0106] Production Example 7 (Production of Polymer B2) 64.34 g of ethanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 15.98 g of methacrylic acid (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 14.02 g of benzyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were placed in a separable flask with a capacity of 300 mL, and degassed by nitrogen bubbling. The contents in the separable flask were then heated to 63°C, and a solution containing 0.66 g of V-65B and 5.00 g of ethanol was added thereto to initiate polymerization. After 6 hours from the start of polymerization, reprecipitation was performed with hexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.). The precipitated polymer was dried in a vacuum at 80°C to obtain polymer B2 (methacrylic acid / benzyl methacrylate copolymer). The content of the structural unit (b1), the content of the structural unit (b2), and the weight average molecular weight of polymer B2 are shown in Table 1.
[0107] Production Example 8 (Production of Polymer B3) Polymer B3 (methacrylic acid / benzyl methacrylate copolymer) was obtained in the same manner as in Production Example 7, except that the amounts of ethanol, methacrylic acid, and benzyl methacrylate initially placed in the separable flask were changed to 64.22 g, 24.44 g, and 5.56 g, and that V-65B was changed to 0.78 g. The content of the structural unit (b1), the content of the structural unit (b2), and the weight average molecular weight of Polymer B3 are shown in Table 1.
[0108] Production Example 9 (Production of Polymer B4) In a 500mL separable flask, 110.90g of ethanol (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), 33.77g of 2-(dimethylamino)ethyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.), and 16.23g of benzyl methacrylate (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.) were placed, and degassed by nitrogen bubbling. The contents in the separable flask were then heated to 63°C, and a solution of 0.76g of V-65B and 5.00g of ethanol was added thereto to initiate polymerization. After 6 hours from the start of polymerization, reprecipitation was performed with hexane (manufactured by FUJIFILM Wako Pure Chemical Industries, Ltd.). The precipitated polymer was vacuum dried at 80°C to obtain polymer B4 (2-(dimethylamino)ethyl methacrylate / benzyl methacrylate copolymer). Table 1 shows the content of the structural unit (b1), the content of the structural unit (b2), and the weight average molecular weight of polymer B4.
[0109] The following polymers were used in the examples and comparative examples other than those mentioned above. Polymer B1: Sodium maleate / diisobutylene copolymer ("ACUSOL 460ND Polymer" manufactured by The Dow Chemical Company) Polymer B'1: Partially neutralized polyacrylic acid ("ACUSOL 445G Polymer" manufactured by The Dow Chemical Company) The weight average molecular weight of the polymer B'1 was measured by gel permeation chromatography under the following measurement conditions. [Measurement conditions] Column: TSKgel G4000PWXL " + "TSKgel G2500PW XL (Tosoh Corporation) Column temperature: 40℃ Eluent: 0.2M phosphate buffer / CH3CN=9 / 1 (volume ratio) Flow rate: 1.0mL / min Detector: Differential refractive index detector Standard material: Pullulan
[0110] Examples 1 to 13, Comparative Examples 1 to 4 Each surface treatment composition was prepared according to the formulation shown in Table 1, and surface treatment was carried out using each surface treatment composition by the following method, followed by the following evaluations. The surface treatment composition was prepared by mixing a betaine polymer having a hydrophobic group as component (A), sodium chloride as component (C), and water, and adding a 1 mass% aqueous solution of an ionic polymer having a hydrophobic group as component (B) that had been previously prepared. Note that component (B) was neutralized with equimolar sodium hydroxide or hydrochloric acid relative to the ionic group before use. In addition, in the case of Comparative Example 1, component (C) was not used, in the case of Comparative Example 2, a betaine polymer (A'1) having no hydrophobic groups was used as component (A), in the case of Comparative Example 3, component (B) was not used, and in the case of Comparative Example 4, a partially neutralized polyacrylic acid (B'1) having no hydrophobic groups was used as component (B). The blending amount of each component in Table 1 is the amount of active ingredient (mass %). (Processing) 10 mL of the prepared surface treatment composition was added to a 300 mL beaker, and the substrate (polypropylene (critical surface tension γ C After immersing a plate (50 mm long x 25 mm wide x 1 mm thick) of 1000 sq. m. (28 dyn / cm) in the solution for 5 minutes, the plate was removed from the solution and rinsed with 200 mL of ion-exchanged water for 10 seconds. The plate was then allowed to stand for 12 hours at 25°C and 50% RH for natural drying to obtain a surface-treated plate.
[0111] (Evaluation of hydrophilic effect) [Contact angle measurement] The static contact angle of each of the surface-treated substrates obtained in Examples 1 to 13 and Comparative Examples 1 to 4 with ultrapure water was measured using an automatic contact angle meter ("DM-701" manufactured by Kyowa Interface Science Co., Ltd.) under conditions of an added amount of 10 μL and 6 seconds after addition. The measurement was performed five times per test piece using two test pieces, and the average of the 10 measured values was recorded as the contact angle in a dry state. The results are shown in Table 1. The smaller the contact angle, the better the hydrophilic performance.
[0112] (Evaluation of compounding stability) The state of each surface treatment composition immediately after preparation of 10 mL of each of the surface treatment compositions prepared in Examples 1 to 13 and Comparative Examples 1 to 4 was visually observed, and the blending stability was evaluated according to the following evaluation criteria. The results are shown in Table 1. A score of 3 on the following evaluation criteria indicates excellent blending stability. A score of 3 on the following evaluation criteria indicates that the composition is particularly suitable for practical use, and a score of 2 on the following evaluation criteria indicates that the composition can be used without any practical problems. [Evaluation Criteria] 3: No precipitates are observed, and the solution is uniform and transparent. 2: Precipitates are observed, but they are fine and uniformly dispersed throughout, resulting in a cloudy appearance. 1: Precipitates are observed, and are locally aggregated (separated) or precipitated.
[0113] (Evaluation of surface appearance after treatment) The presence or absence of precipitates on the surface of each of the surface-treated substrates obtained in Examples 1 to 13 and Comparative Examples 1 to 4 was visually observed, and the surface appearance after treatment was evaluated according to the following evaluation criteria. The results are shown in Table 1. A grade of A in the following evaluation criteria is suitable for practical use. [Evaluation Criteria] A: No precipitates were observed, and the surface was uniform and transparent. B: Precipitation is observed and the surface is whitish and dull.
[0114] [Table 1]
[0115] From Table 1, it can be seen that the surface treatment compositions of the Examples have smaller contact angles, higher hydrophilicity effects, and excellent blend stability compared to the Comparative Examples, and can form treated surfaces with good appearances. [Industrial Applicability]
[0116] According to the present invention, when applied to a solid surface having low surface free energy, even when the treated solid surface is dried under conditions with a slow drying rate, such as natural drying, it is possible to impart high hydrophilicity to the solid surface without impairing the surface appearance of the treated solid.
Claims
1. The following components (A), (B), and (C): (A) A polymer containing at least a structural unit (a1) having a betaine group, a structural unit (a2) having an ionic group, and a structural unit (a3) having a hydrophobic group. (B) A polymer including at least a structural unit (b1) having an ionic group having an opposite charge to the charge of the ionic group of the structural unit (a2), and a structural unit (b2) having a hydrophobic group. (C) Electrolyte A surface treatment composition comprising:
2. 2. The surface treatment composition according to claim 1, wherein the structural unit (a1) is a structural unit having a betaine group represented by the following formula (1): 【Chemistry 1】 [In formula (1), R 1 ~R 3 are the same or different and each represents a hydrogen atom or an alkyl group having 1 or 2 carbon atoms, R 4 represents an alkylene group having 1 to 4 carbon atoms, or -Y 1 -OPO 3 - -Y 2 - indicates Y 1 and Y 2 are the same or different and represent an alkylene group having 1 to 4 carbon atoms, R 5 and R 6 are the same or different and represent a hydrocarbon group having 1 to 4 carbon atoms, X 1 is an oxygen atom or NR 7 R 7 represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, X 2 is R 4 is an alkylene group having 1 to 4 carbon atoms, R 17 SO 3 - , or R 17 COO - indicates R 17 represents an alkylene group having 1 to 4 carbon atoms which may have a hydroxyl group; X 2 is R 4 Ga-Y 1 -OPO 3 - -Y 2 When it is -, it represents a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms.
3. The surface treatment composition according to claim 1 or 2, wherein the content of the component (C) is 0.1 mass % or more and 15 mass % or less.
4. The surface treatment composition according to any one of claims 1 to 3, wherein the mass ratio [(B) / (A)] of the content of the component (B) to the content of the component (A) is 0.001 or more and 1 or less.
5. The surface treatment composition according to any one of claims 1 to 4, wherein the content of the structural unit (a3) having a hydrophobic group in all structural units of the component (A) is from 0.02 mol % to 30 mol %.
6. The surface treatment composition according to any one of claims 1 to 5, wherein the content of the structural unit (a2) having an ionic group in all structural units of the component (A) is 0.02 mol % or more and 30 mol % or less.
7. The surface treatment composition according to any one of claims 1 to 6, wherein the content of the structural unit (b2) having a hydrophobic group in all structural units of the component (B) is 0.02 mol % or more and 70 mol % or less.
8. The surface treatment composition according to any one of claims 1 to 7, wherein the total content of component (A) and component (B) is 0.05 mass% or more and 15 mass% or less.
9. A surface treatment method, comprising applying the surface treatment composition according to any one of claims 1 to 8 to a solid surface having a surface free energy of less than 45 dyn / cm.
Citation Information
Patent Citations
Hydrophilization treatment agent composition
JP2019094434A
Solid surface hydrophilizing method
JP2022161634A